2021
DOI: 10.3390/pathogens10080975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Expression of Classical Enterotoxin Genes among Staphylococci Associated with Bovine Mastitis

Abstract: Staphylococcal food poisoning (SFP), caused by the contamination of staphylococcal enterotoxins, is a common foodborne disease worldwide. The aims of this study were: (1) to investigate classical staphylococcal enterotoxin genes, sea, seb, sec, sed, and see, among Staphylococcus aureus and coagulase-negative staphylococci (CNS) associated with bovine mastitis; (2) to determine the effect of temperature on the expression of classical staphylococcal enterotoxin genes in staphylococci in milk. The detection of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…Enterotoxin C (Sec) gene was the only classical enterotoxin gene detected in CoNS species isolates in the present study. The nding was in agreement with the report of Homsombat et al [39], Banaszkiewicz et al [40], Nasaj et al [41] who reported a higher enterotoxin C (Sec)…”
Section: Discussionsupporting
confidence: 93%
“…Enterotoxin C (Sec) gene was the only classical enterotoxin gene detected in CoNS species isolates in the present study. The nding was in agreement with the report of Homsombat et al [39], Banaszkiewicz et al [40], Nasaj et al [41] who reported a higher enterotoxin C (Sec)…”
Section: Discussionsupporting
confidence: 93%
“…Londrina, v. 43, n. 5, p. 2309-2322, set./out. 2022 milk processing and/or transportation can occur (Homsombat et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies indicate that temperature and pH might also influence the expression of genes that code for the production of enterotoxins [ 36 , 37 ]. A study shows that the production of SEA can usually be detected at 10–45 °C and the yield of SEA increases with the increasing temperature [ 33 , 38 ]. A study indicated that the conditions for SEA production were pH of > 5.0 and aw of > 0.86 at temperatures of > 15 °C [ 36 ].…”
Section: Discussionmentioning
confidence: 99%